Comparative Outcomes of Preoperative Chemoradiotherapy and Selective Postoperative Chemoradiotherapy in Clinical Stage T3N0 Low and Mid Rectal Cancer. Issue 7 (3rd October 2019) - Lin, Yu; Lin, Huiming; Xu, Zongbin; Zhou, Sunzhi; Chi, Pan
Abstract: Purpose/aim : Preoperative chemoradiotherapy (pre-CRT) and total mesorectal excision (TME) have become the standard of care for patients with locally advanced rectal cancer (LARC). Nevertheless, it is a controversial issue whether pre-CRT in cT3N0M0 patients would result in potential overtreatment. Materials and methods : In total, 183 clinical stage IIA rectal cancer patients treated with and without pre-CRT between 2011 and 2014 were retrospectively analyzed. Capecitabine/FOLFOX/CAPOX chemotherapy was co-administered with preoperative radiotherapy. Surgical resection with laparoscopic or open TME was conducted 8–12 weeks after completion of the pre-CRT. Postoperative radiotherapy was routinely given to patients with pT4 lesion or circumferential margin (CRM) and/or distal resection margin (DRM) involvement. Results : In total, 108 (59%) patients received pre-CRT and 75 (41%) underwent surgery first. The pre-CRT patients presented with less-advanced pathological T stage tumors compared with the surgery-first patients ( p < 0.001). However, the pathological N stage was not significantly different between the two groups ( p = 0.065). The 3-year overall survival (OS), disease-free survival (DFS), and 2-year local recurrence (LR) rate were similar in the pre-CRT and surgery-first patients (88.4 versus 88.7%, p = 0.552; 79.6 versus 83.3%, p = 0.797; 2.8 versus 2.7%, p = 0.960, respectively). Cox regression analysis showed that pN stage and CRM/DRM involvement were independently correlated with an unfavorable DFS. Conclusions : In this study, the omission of pre-CRT in cT3N0M0 patients did not translate into a worse oncological outcome. Postoperative radiotherapy should remain a standard option for patients with CRM/DRM involvement and pathological T4 tumors. A generalized indication for pre-CRT in cT3N0 patients is likely to result in overtreatment.